Immunomodulatory and biological properties of helminth-derived small molecules: Potential applications in diagnostics and therapeutics - Yeshi, Karma; Ruscher, Roland; Loukas, Alex; Wangchuk, Phurpa (Frontiers in Parasitology, 2022)
Parasitic helminths secrete and excrete a vast array of molecules known to help skew or suppress the host's immune response, thereby establishing a niche for sustained parasite maintenance. Indeed, the immunomodulatory potency of helminths is attributed mainly to excretory/secretory products (ESPs). The ESPs of helminths and the identified small molecules are reported to have diverse biological and pharmacological properties. The available literature reports only limited metabolites, and the identity of many metabolites remains unknown due to limitations in the identification protocols and helminth-specific compound libraries. Many metabolites are known to be involved in host-parasite interactions and pathogenicity. For example, fatty acids (e.g., stearic acid) detected in the infective stages of helminths are known to have a role in host interaction through facilitating successful penetration and migration inside the host. Moreover, excreted/secreted small molecules detected in helminth species are found to possess various biological properties, including anti-inflammatory activities, suggesting their potential in developing immunomodulatory drugs. For example, helminths-derived somatic tissue extracts and whole crude excretory/secretory products showed anti-inflammatory properties by inhibiting the secretion of proinflammatory cytokines from human peripheral blood mononuclear cells and suppressing the pathology in chemically-induced experimental colitis mice models. Unlike bigger molecules like proteins, metabolites are ideal candidates for drug development since they are small structures, malleable, and lack immunogenicity. Future studies should strive toward identifying unknown molecules and isolating the under-explored niche of helminth metabolites using the latest metabolomics technologies and associated software, which hold potential keys for finding new diagnostics and novel therapeutics.